Cover Image. (20th February 2020) - Azimi, Mohammad S.; Motherwell, Jessica M.; Hodges, Nicholas A.; Rittenhouse, Garret R.; Majbour, Dima; Porvasnik, Stacey L.; Schmidt, Christine E.; Murfee, Walter L.
Abstract : Cover Caption: The cover image is based on the Original Article Lymphatic‐to‐Blood Vessel Transition in Adult Microvascular Networks: A Discovery Made Possible by a Top‐Down Approach to Biomimetic Model Development by Walter Murfee et al., https://doi.org/10.1111/micc.12595 .